UPAYA PEMERINTAH DAERAH DALAM MENINGKATKAN PENDIDIKAN DI KOMUNITAS ADAT TERPENCIL DESA SESAP KECAMATAN TEBING TINGGI KABUPATEN KEPULAUAN MERANTI TAHUN 2011 – 2014 - M. Viqy Saputra Misya; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This paper aims to determine Efforts of Local Government in Improving Education in Remote Indigenous Communities Village Sesap District of Tebing Tinggi District Meranti Islands Year 2011 - 2014 and Factors - Factors hindering the efforts of Local Government in Improving Education in Remote Indigenous Communities Village Sesap District of Tebing Tinggi District Meranti Islands in 2011 - 2014. the research method used in this study with the type of case studies and field research. The research approach with a qualitative approach to the type of data used primary data and secondary data, the data sources obtained from the informant research, mass media, and documentation. Data were collected by interview, and search document, and then analyzed by the case method and field research to learn intensively about the background of current affairs and environmental interactions appropriate social unit. The results showed that the efforts of Local Government in Improving Education in Remote Indigenous Communities Village sesap still not optimal because there are still so many people the Remote Indigenous Communities that do not follow the program package A, B and program Functional Literacy and Skills Functional in Center Community Learning Center, and scholarships for poor students is not used well by the parents, by used for daily needs and not used for their children school supplies, local government should be more selective again making policy these scholarships , While a student hostel tribal / KAT is not functioning optimally because only a few KAT who want to continue schools and stay in this hostel, the local government should further improve the dissemination make the community more aware of the importance of education / schooling, in order to motivate and sensitize the parents on Remote Indigenous Communities this will be the importance of education of their children, due to lack of education caused ignorance the parents.Keywords: Effort, Education, Remote Indigenous Communities